Influence of the aperiodic component on the short circuit current in electric power system; AIP Conference Proceedings; Vol. 2212 : Thermophysical Basis of Energy Technologies (TBET 2019) - Suvorov A. A. Aleksey Aleksandrovich (2020, 2020)
Title screen